2018
DOI: 10.1038/s41598-018-25827-5
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants implicate cardiac function and development pathways in earthquake-induced stress cardiomyopathy

Abstract: The pathophysiology of stress cardiomyopathy (SCM), also known as takotsubo syndrome, is poorly understood. SCM usually occurs sporadically, often in association with a stressful event, but clusters of cases are reported after major natural disasters. There is some evidence that this is a familial condition. We have examined three possible models for an underlying genetic predisposition to SCM. Our primary study cohort consists of 28 women who suffered SCM as a result of two devastating earthquakes that struck… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…The anecdotally described concurrent onset of TS in close relatives illustrates that there must be some biological background that in conjunction with an external trigger finally results in development of TS. Genetic studies have already identified promising loci, copy number variations, and polymorphisms in TS patients [33][34][35][36][37][38][39]; however, these results require further confirmation and exploration before allowing for mechanistic conclusions. Another key toward understanding the pathogenesis of TS might be hidden in the striking gender preponderance: 90% of patients are women, and of those 80% are postmenopausal.…”
Section: Spasm Catecholamines Gender and The Brainmentioning
confidence: 99%
“…The anecdotally described concurrent onset of TS in close relatives illustrates that there must be some biological background that in conjunction with an external trigger finally results in development of TS. Genetic studies have already identified promising loci, copy number variations, and polymorphisms in TS patients [33][34][35][36][37][38][39]; however, these results require further confirmation and exploration before allowing for mechanistic conclusions. Another key toward understanding the pathogenesis of TS might be hidden in the striking gender preponderance: 90% of patients are women, and of those 80% are postmenopausal.…”
Section: Spasm Catecholamines Gender and The Brainmentioning
confidence: 99%
“…Current research has investigated possible associations between TTS and single nucleotide polymorphisms (SNPs) in genes involved with sympathetic stress. Various studies have been published describing SNPs potentially implicated in the pathogenesis of TTS ( Table 2 ) [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current research has investigated possible associations between TTS and single nucleotide polymorphisms (SNPs) in genes involved with sympathetic stress. Various studies have been published describing SNPs potentially implicated in the pathogenesis of TTS (Table 2) [31][32][33][34][35][36][37][38][39][40][41][42][43]. The prevalence of polymorphisms of ADRB1, ADRB2, and GNAS were similar between patients and controls.…”
Section: Gwas and Polymorphism Studiesmentioning
confidence: 96%
“…Current literature has focused on the possible existence of associations between TTS and single nucleotide polymorphisms (SNPs) in genes associated with sympathetic stress. Several studies analysing polymorphisms potentially involved in the pathogenesis of TTS have been published (Table 2) [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Gwas and Polymorphism Studiesmentioning
confidence: 99%
“…The exome sequencing may be used for identifying causal variants of rare disorders by using the Next Generation Sequencing (NGS) technology. Exome analysis, genotyping array analysis, and array comparative genomic hybridization were carried out on 28 Christchurch EqSCM cases [33].…”
Section: Gwas and Polymorphism Studiesmentioning
confidence: 99%